Organizational Justice & Work Climate of Hotel Employees in Sarawak, Malaysia - Mark, Kasa; Zaiton, Hassan (Guiness Press, 2024)
Research Aims The purpose of this study was conducted to investigate the relationship between both organizational justice and organizational climate towards turnover intention, with job satisfaction acting as the mediating variable.